In Patients with Established RA, Positive Effects of a Randomised Three Month WBV Therapy Intervention on Functional Ability, Bone Mineral Density and Fatigue Are Sustained for up to Six Months - Prioreschi, A.; Makda, M.; Tikly, M.; McVeigh, Joanne (Public Library of Science, 2016)
Functional ability is often impaired for people with rheumatoid arthritis (RA), rendering these patients highly sedentary. Additionally, patients with RA often take medication known to negatively affect bone mass. Thus improving functional ability and bone health in this group of patients is important. The aim of this study was to investigate the effects of whole body vibration (WBV) therapy in patients with stable, established RA. Thirty one females with RA were randomly assigned to a control group (CON, n = 15) who continued with their normal activities or a WBV group (n = 16) who underwent a three month WBV therapy intervention, consisting of 15 minutes of intermittent vibration, performed twice per week. Patients were assessed at baseline, three months, and three months post intervention for functional ability using the modified Health Assessment Questionnaire; for RA disease activity using the Clinical Disease Activity Index, for quality of life using self-report fatigue and pain scores; for physical activity profiles using accelerometry, and for BMD and body composition using DXA. Patients in both groups were matched for all variables at baseline. After the intervention period, functional ability was significantly improved in the WBV group (1.22(0.19) to 0.92(0.19), p = 0.02). Hip BMD was significantly reduced in the CON group (0.97(0.05) to 0.84(0.05) g.cm-2, p = 0.01), while no decreases were seen in the WBV group (1.01(0.05) to 0.94(0.05) g.cm-2, p = 0.50). Despite no change in RA disease activity in either group at either follow up, fatigue levels were improved in the WBV group (4.4(0.63) to 1.1(0.65), yet remained unchanged in the CON group at both follow ups (p = 0.01). Ten minute bouts of light to moderate physical activity were significantly reduced in the CON group after the intervention (2.8(0.61) to 1.8(0.64) bouts per day, p = 0.01), and were preserved in the WBV group (3.1(0.59) to 3.0(0.61) bouts per day, p = 0.70). Intermittent WBV shows promise for sustained improvements in functional ability, for attenuating loss of bone mass at the hip, as well as for decreasing fatigue in patients with established RA. TRIAL REGISTRATION: Pan African Clinical Trials Registry PACTR201405000823418.